2004
DOI: 10.1023/b:cemn.0000036402.79129.2f
|View full text |Cite
|
Sign up to set email alerts
|

The Stroke-Prone Spontaneously Hypertensive Rat: How Good Is It as a Model for Cerebrovascular Diseases?

Abstract: 1. Cerebrovascular diseases (CVDs) in humans are a mixture of diseases with different etiologies. 2. Although the stroke-prone spontaneously hypertensive rat (SHRSP) cannot represent all types of CVDs, it is probably a good genetic model for particular types such as lacunar infarction and intracerebral hemorrhage. 3. Genetic studies suggested that SHRSP has genetic susceptibility to stroke independent of its severe hypertension. Studies on SHRSP may provide useful information with which to dissect genetic susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 19 publications
3
33
0
3
Order By: Relevance
“…It is, instead, similar to brain edema due to malignant hypertension and lacunar infarction, and cerebral hemorrhage caused by arteriosclerosis or hyalinosis of small arteries due to severe hypertension. 34 Besides hypertension, additional genetic factors were implicated in the stroke susceptibility of SHRSP, such as neuronal vulnerability to ischemic insult, dysfunctional blood-brain barrier and arterial histological abnormalities. 34 QTL studies were performed on infarction tissue volume after artificial middle cerebral artery occlusion and stroke latency.…”
Section: Genetic Studies On Hypertension and Cerebral Stroke In Shrspmentioning
confidence: 99%
See 1 more Smart Citation
“…It is, instead, similar to brain edema due to malignant hypertension and lacunar infarction, and cerebral hemorrhage caused by arteriosclerosis or hyalinosis of small arteries due to severe hypertension. 34 Besides hypertension, additional genetic factors were implicated in the stroke susceptibility of SHRSP, such as neuronal vulnerability to ischemic insult, dysfunctional blood-brain barrier and arterial histological abnormalities. 34 QTL studies were performed on infarction tissue volume after artificial middle cerebral artery occlusion and stroke latency.…”
Section: Genetic Studies On Hypertension and Cerebral Stroke In Shrspmentioning
confidence: 99%
“…34 Besides hypertension, additional genetic factors were implicated in the stroke susceptibility of SHRSP, such as neuronal vulnerability to ischemic insult, dysfunctional blood-brain barrier and arterial histological abnormalities. 34 QTL studies were performed on infarction tissue volume after artificial middle cerebral artery occlusion and stroke latency. Rubattu et al 35,36 identified QTLs for stroke latency on Chr 1, 4 and 5 in an F2 intercross between SHRSP/Bbb and SHR/Bbb, of which the QTL on Chr 1 was confirmed in congenic strains.…”
Section: Genetic Studies On Hypertension and Cerebral Stroke In Shrspmentioning
confidence: 99%
“…Further, we clearly showed an uneven distribution of DND in CA1. The quantitative evaluation employed here may be useful in the genetic analysis of DND in SHRSP (Nabika et al 2004). In addition, this method is probably useful in the precise evaluation of the effects of medical treatments on the 'ischemia/reperfusion' insult (Qiang et al 1989;Yamashita et al 1993Yamashita et al , 1994.…”
Section: Discussionmentioning
confidence: 99%
“…As SHRSP is a model of cerebral stroke, the vulnerability to DND may be one of the phenotypic representations of its genetic susceptibility to cerebral stroke (Nabika et al 2004). The quantitative evaluation of DND will promote the study of genetic analysis of DND in this unique model strain.…”
Section: Discussionmentioning
confidence: 99%
“…The stroke-prone spontaneously hypertensive rat (SHRSP) is a good genetic model for particular types of stroke. These rats develop stroke even when placed on normal diets because of their genetic susceptibility to stroke (31). However, the above-mentioned models represent individual risk factors and a more comprehensive model that incorporates all of these pathologies is needed.…”
Section: █ Conclusionmentioning
confidence: 99%